Improving Active Questioning and Learning Outcomes on Social Studies through Make a Match Learning Model in Class IX C SMP N 7 Purwokerto in the First Semester of the Academic Year 2014/2015 (Forum Ilmu Sosial, 2021)
This study aims to increase active questioning and learning outcomes of class IX C students by using the Make a Match learning model. This is classroom action research carried out in three cycles. Each cycle has various stages, namely planning, implementation, observation and reflection. The Make a Match learning model has been proven to increase students' active questioning and learning outcomes. It is indicated by the learning outcomes data in the Cycle I with details of the highest score of 100, the lowest score of 49, the average score of 69.65, and the completeness score of 66.67%. In the Cycle II, the learning outcomes data show the highest score is 100, the lowest score is 69, the average score is 92.95, and the completeness score is 82.80%. Furthermore, in Cycle III, the data exemplify that the highest score is 100, the lowest score is 61, the average score is 86.21, and the completeness score is 89.66 %. These points indicate that the use of the Make a Match learning model can improve the active questioning and the learning outcomes of class IX C students of SMP N 7 Purwokerto in the first semester of the academic year 2014/2015.